Does administrative support negate the consequences of nurse abuse?. (27th February 2015) - Azar, Mathilde; Badr, Lina Kurdahi; Samaha, Helen; Dee, Vivien
Abstract : Aim: To assess the relationship between disruptive/abusive situations and the 'intention to leave' nursing. Background: While every nurse deserves to feel safe in his or her working environment, nurse abuse remains a common occurrence worldwide. Only when hospitals are safe, is retention enhanced and patient care improved. Method: A cross‐sectional survey was conducted with 1053 nurses. Results: Almost 70% of nurses experienced stressful disruptive/abusive situations that were mainly caused by patients/families. The majority felt skilled in dealing with these situations, yet around 40% considered leaving nursing because of disruption/abuse. Stress from disruption/abuse, the skill in dealing with abuse and the administrations' support were the best predictors for the 'intention to leave'. Conclusions: It may not be the amount of abuse per se that affects the nurses' intention to leave, but rather how the abuse is perceived, the skill in dealing with it and the support received from administration. Implications for nursing management: The support received from nursing administration may negate the effect of stress and the 'intention to leave' because of disruptive/abusive situations. This should behove nurse managers and administrators to have a system in place to provide support for nurses, which in turn could improve job satisfaction and retention.